Penerapan Terapi Akupresur untuk Meningkatkan Kekuatan Otot pada Pasien Stroke - Veni Budi Lestari; Sri Indaryati; Novita Elisabeth Daeli (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Stroke is a serious neurological disorder. A stroke is an acute attack that can cause death or disability, both physically and mentally. Muscle weakness is one of the most common clinical signs experienced by stroke patients. One way to prevent permanent disability in stroke patients is to train muscle strength through acupressure therapy. This study aims to analyze the application of nursing care through acupressure therapy in improving muscle strength in stroke patients. The method used is a case study using a descriptive one-group research method with a pre-test-post-test design on three stroke patients with an intervention of 7 consecutive days with a frequency of 2 times a day for a duration of 12 minutes. The results showed that respondent I's muscle strength before therapy was on a scale of 3 and post-therapy was on a scale of 4, respondent II's pre-therapy was on a scale of 1 and post-therapy was on a scale of 1, and respondent III's pre-therapy was on a scale of 3 and post-therapy was on a scale of 4. It was concluded that acupressure therapy is effective as an additional therapy in nursing practice to help improve muscle strength in stroke patients.